Analisis Dekomposisi Produktivitas di Sektor Industri Kimia Indonesia: Pendekatan Malmquist Productivity Index - Bernadetta Dwi Suatmi (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2020)
This research aims to investigate the pattern of and decompose the growth of total factor productivity (TFP) in the Indonesian chemical industry (ISIC 35) during the period of trade reform (1981-2000). Using data envelopment analysis (DEA) output-oriented Malmquist productivity index, TFP growth can be decomposed into efficiency change and technological change. Results of the two-digit level of the chemical industry show that generally, the growths of TFP were positive during all sample periods, with the main driver being efficiency change. The exception was in the sub-period of further reform (1992-1996), where TFP growth was negative. These results are similar to the analysis of three-digit levels in sub-periods. Exceptions are in combined industries of other chemical industries (ISIC 352) and industrial chemical industries (ISIC 351) and plastic industries (ISIC 356), where TFP growths were negative in the sub-period of further reform). The implication of this study shows that trade reform policy may have a different effect across sub-sectors and sub-periods in the Indonesian chemical industry. Keywords: data envelopment analysis method, Malmquist productivity index, Indonesia, chemical industry References: Abramovitz, M. (1956). Resource and Output Trends in the United States Since 1870. The American economic review, 46(2), 5-23. doi:10.2307/1910656 Amiti, M., & Konings, J. (2007). Trade Liberalization, Intermediate Inputs, and Productivity: Evidence from Indonesia. American Economic Review, 97(5), 1611-1638. doi:10.1257/aer.97.5.1611 Angeriz, A., McCombie, J., & Roberts, M. (2006). Productivity, efficiency and technological change in European Union regional manufacturing: A data envelopment analysis approach. The Manchester School, 74(4), 500-525. Aswicahyono, H. H., Bird, K., & Hill, H. (1996). What Happens to Industrial Structure When Countries Liberalise? Indonesia since the mid-1980s. Journal of development studies, 32(3), 340. Retrieved from http://search.ebscohost.com/login.aspx?direct=true&db=bth&AN=9603062868&site=ehost-live Caves, D. W., Christensen, L. R., & Diewert, W. E. (1982). The Economic Theory of Index Numbers and the Measurement of Input, Output, and Productivity. Econometrica 50(6), 1393-1393. Retrieved from http://search.proquest.com/docview/214655014?accountid=10382 Coelli, T. (1996). A guide to DEAP version 2.1: a data envelopment analysis (computer) program. Centre for Efficiency and Productivity Analysis, University of New England, Australia, 96(08), 1-49. Coelli, T., Rao, D. S. P., & Battese, G. E. (2005). An Introduction to Efficiency and Productivity Analysis (2nd ed.). New York: Springer. FÃ¤re, R., Grosskopf, S., Norris, M., & Zhongyang, Z. (1994). Productivity Growth, Technical Progress, and Efficiency Change in Industrialized Countries. (cover story). American Economic Review, 84(1), 66-83. Retrieved from http://search.ebscohost.com/login.aspx?direct=true&db=bth&AN=9406080294&site=ehost-live Farrell, M. J. (1957). The Measurement of Productive Efficiency. Journal of the Royal Statistical Society. Series A (General), 120(3), 253-290. Retrieved from http://www.jstor.org/stable/2343100 Gatto, M. D., Liberto, A. D., & Petraglia, C. (2009). Measuring Productivity. Working Paper, 05(01), 1-59. Griliches, Z. (1960). Measuring Inputs in Agriculture: A Critical Survey. Journal of Farm Economics, 42(5), 1411-1427. doi:10.2307/1235702 Halim, R. E. (2010). Marketing productivity and profitability of Indonesian public listed manufacturing firms: an application of data envelopment analysis (DEA). Benchmarking: An International Journal. Ikhsan, M. (2007). Total Factor Productivity Growth in Indonesian Manufacturing: A Stochastic Frontier Approach. Global Economic Review, 36(4), 321-342. doi:10.1080/12265080701694488 Isaksson, A. (2009). The UNIDO World Productivity Database: An Overview. International Productivity Monitor, 18, 38-50. Retrieved from https://EconPapers.repec.org/RePEc:sls:ipmsls:v:18:y:2009:3 Mahadevan, R. (2003). To Measure or Not To Measure Total Factor Productivity Growth? Oxford Development Studies, 31(3), 365-378. doi:10.1080/1360081032000111742 Margono, H., & Sharma, S. C. (2006). Efficiency and Productivity Analyses of Indonesian Manufacturing Industries. Journal of Asian Economics, 17(6), 979-995. doi:10.1016/j.asieco.2006.09.004 Narjoko, D., & Hill, H. (2007). Winners and Losers During a Deep Economic Crisis: Firm-level Evidence from Indonesian Manufacturing. Asian Economic Journal, 21(4), 343-368. doi:10.1111/j.1467-8381.2007.00261.x Prabowo, T. H. E., & Cabanda, E. (2011). Stochastic frontier analysis of Indonesian firm efficiency: A note. International Journal of Banking and Finance, 8(2), 74-91. Saputra, P. M. A. (2011). Analysis of technical efficiency of Indonesian manufacturing industries: An application of DEA. International Research Journal of Finance and Economics, 66(1), 107-116. Shephard, R. W. (1970). Theory of Cost and Production Functions. Princeton: Princeton University Press. Solow, R. M. (1957). Technical Change and the Aggregate Production Function. The Review of Economics and Statistics, 39(3), 312-320. doi:10.2307/1926047 Surjaningsih, N., & Permono, B. P. (2014). Dinamika total factor productivity industri besar dan sedang Indonesia. Buletin Ekonomi Moneter dan Perbankan, 16(3), 277-308. Suyanto, & Salim, R. (2013). Foreign Direct Investment Spillovers and Technical Efficiency in the Indonesian Pharmaceutical Sector: Firm-Level Evidence. Applied Economics, 45(3), 383-395. doi:10.1080/00036846.2011.605554 Swan, T. W. (1956). Economic Growth and Capital Accumulation. Economic Record, 32, 334-361. Timmer, M. P. (1999). Indonesia's Ascent on the Technology Ladder: Capital Stock and Total Factor Productivity in Indonesian Manufacturing, 1975â€“95. Bulletin of Indonesian economic studies, 35(1), 75-97. doi:10.1080/00074919912331337497 Vial, V. (2006). New Estimates of Total Factor Productivity Growth in Indonesian Manufacturing. Bulletin of Indonesian economic studies, 42(3), 357-369. doi:10.1080/00074910601053227 Zrelli, H., Alsharif, A. H., & Tlili, I. (2020). Malmquist Indexes of Productivity Change in Tunisian Manufacturing Industries. Sustainability, 12(4), 1367.